(3eMGVQGJ aj GdehGRfI GdYGeIs - (3Yaja GdebOe(B, (3GdbGVjs ((3HjQhJ(B:s (3GdOGQ GdLGeYjI(B,s, 2000)
(3GdOSJhQ h GdfUhU GdeGdjI eY CHQR NUGFU GdehGRfI GdYGeI , eHOC GdTehd hGdTjhY eHOCSfhjI GdehGRfI , eHOC hMOI GdehGRfI, GYOGO GdehGRfI , bQGQ GdehGRfI ,JfajP GdehGRfI , edGGbHI JfajP GdehJRfIs
Keywords: (3GdOSJhQs; (3GdehGRfIs